Pengembangan Modul Ipa Berbasis Integrasi Islam Dan Sains Dengan Pendekatan Inkuiri Di Mi Salafiyah Kutukan Blora - Silviana Nur Faizah (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2017)
Abstract: The aims of this research is to design Science module based Islam and Science integration by inquiry effevctivaly, valid, and interest for 3rd grade student of MI Slafiyah Kutukan Blora. This research is Educational research uses models Walter Dick and Lou Carey development type. The subjects of assesmnet in this module are master of contain, master of design, master of language, master oflearning, also 3rd grde student of MI Slafiyah kutukan Blora. The main step of this research is analyzing pre-condition, development modul plan, module writting, and module assesment.The result of reasearch find that Science Module based Islam and Science integration has contain validity level 84%, desain validity 86 %, language validity 75%, learning validity 95%. This module is effectif base on independent sample t test calculation thitung (1,71)>ttabel(1,684).  While level of student interest using the module for all of componet until 88% exellent score.  Based on whole anlizing data result can conclud that Science Module based Islam and Science integration is valid, effectiv, and interest for 3rd grade of MI Salafiyah Kutukan Blora.Keyword: Module, Islam and Science Integration, Inquiry